Collaborative Governance and Strengthening Household Resilience in Faching Disaster at Ciliwung Riverbank, Jakarta City - Irwan, Irwan; Zusmelia, Zusmelia; Siska, Felia; Elvawati, Elvawati; Melia, Yenni (Humanus, 2022)
The focus of this study is to analyze collaborative governance and strengthening household resilience to disasters. The theory used is the collaborative governance theory from Emerson et.al and the household resilience theory from Karbon et.al. This research uses a mix method research approach. Data collection techniques started from participant observation techniques, in-depth interviews, unstructured discussions, survey techniques and group interview methods. The unit of analysis in this study were individuals and households at the RW and RT levels. This study used  data analysis of the Miles and Huberman model in qualitative analysis and Importance Performance Analysis (IPA) analysis in quantitative approach. The results of this study showed  that households at  the Ciliwung Riverbank remain resilient in disaster areas due to their success in building cooperation and creating new behaviors. Cooperation was carried out not only at the household level but also at the national level. This success showed that households were  able to take action together, carry out risk reduction activities and are able to increase the capacity of economic life in the household. The novelty in this study is that collaborative governance creates new behaviors to reduce the impact of disasters and strengthen household resilience to stay in the disaster area.